An investigation of zootherapy in the Roman world - Rolph, Rachel (2023)
Zootherapy is the use of living or dead animals and their parts and products for medical or healing purposes. Although practised across the world and throughout time, a post-Enlightenment, Western aversion to ‘unscientific’ and ‘irrational’ medical methods has hindered our understanding of zootherapy both past and present. This has caused archaeologists to be unaware of, or less receptive to, the possibilities of identifying the evidence of zootherapy in the Roman archaeological record. To counter this, this dissertation will promote zootherapy as a valid interpretation of zooarchaeological material, and will outline methods that could be used to identify the archaeological evidence of zootherapy from the Roman world. It will begin with an exploration of current zootherapy that will highlight the commonalities between the processes used in different countries. The Roman conception of medicine will then be discussed, with special attention paid to the ways in which food, religion and magic overlap with healing practices. Recognising this overlap is important for understanding the roles of animals in different aspects of Roman medicine, as they can be found in temples, diets, and amulets. Finally, the ways in which it might be possible to identify Roman zootherapy in the archaeological record will be discussed.